Priorities for Further Fiscal Reforms in the Commonwealth of Independent States - Lorie, Henri (Washington, D.C. : International Monetary Fund, 2003)
Building on the substantial progress made in establishing fiscal systems consistent with market economies, the paper identifies priorities for further fiscal structural reforms among the Commonwealth of Independent States (CIS) countries. Activities of extra budgetary accounts and quasi-fiscal activities need to be brought into the budget framework. Although there is room for improvements, the CIS countries now have, broadly, levels of tax revenues and expenditures not out of line with the international norm, taking into account income levels. The main challenges they face are to further increase the market friendliness of taxation and to implement an efficiency-improving structural reform of the expenditure system while strengthening control and accountability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet